The Work Environment and Its Influence on Learning Transfer in Virtual In-Service ICT Training for Teachers and University Professors - Fernanda Fauth; Juan González-Martínez (MDPI AG, 2023)
This study seeks to analyse which factors in the work environments of students undergoing virtual in-service ICT teacher training facilitate the initial transfer of learning. Deductive categories were first defined based on previous studies. A qualitative analysis was then conducted to triangulate three data sources-two reflective training activities and interviews with students-using NVivo 12 software. This enabled us to determine how important some of these factors are for learning transfer within the context of techno-pedagogical distance teacher training, such as the predominance of social support over organizational categories.